Optimalisasi Prinsip Kerahasiaan Data Nasabah dan Peranan Otoritas Jasa Keuangan Dalam Mencegah Kebocoran Informasi - Isnugraheny, Rizqika Farah; Megawati, Zahra Ekasiwi; Susilawati, Siti (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The principle of customer data confidentiality is a key pillar in maintaining trust and integrity within the financial services sector. With the advancement of digital technology and the increasing threat of data breaches, optimizing customer data protection has become a critical issue. This study examines the efforts to optimize the principle of customer data confidentiality through the implementation of effective policies and the role of the Financial Services Authority (OJK) as the main regulator and supervisor in Indonesia. OJK plays a key role in setting data security standards, overseeing regulatory implementation, and ensuring that financial service providers comply with good governance principles. This study also analyzes various data breach cases that have occurred, as well as preventive measures that can be taken, such as strengthening security systems, educating financial service providers, and imposing strict sanctions for violations. The findings suggest that collaboration between OJK, financial service providers, and other stakeholders is crucial in creating a safe, transparent, and trustworthy financial ecosystem. Optimizing customer data confidentiality not only protects consumer rights but also strengthens the stability of the national financial sector in the digital era.